IMPLEMENTASI MODEL PEMBELAJARAN TWO STAY TWO STRAY DALAM PEMBELAJARAN BERBASIS KEMAMPUAN BERPIKIR KRITIS KELAS V SD - Wardana, M. Yusuf Setia; Arumatika, Nindi (Universitas Pendidikan Indonesia, 2017)
Benefits of mathematics are to equip students with the ability to think logically, analytical, systematically, critically, and creatively, as well as the ability to cooperate. Based on observations in elementary school, there are 40% of students have not reached KKM and students have lack of critical abilities to understand math problems, and they have low activity of the study. One of models that can be applied is Two Stay Two Stray. The study used True Experimental Design with Posttest-Only Control Design. The population in this study was all fifth grade students of SD Negeri Semarang Rejosari 03. Data of critical thinking skills of the students in average on test of critical thinking skills mastery was 3.31 ≥ 2.67, it can be said to have a complete description. The conclusion is a model of Two Stay Two Stray being effective for critical thinking skills and mathematics learning outcomes of fifth grade students in SD Negeri Rejosari 03 Semarang.Keywords: two stay two stray model, critical thinking ability.